Patterns of Clinically Identifiable Congenital Defects in Neonates - Basnet, Sahisnuta; Gauchan, Eva; Shrestha, Junu; Jha, Jyoti (Journal of Nepal Health Research Council, 2021)
Background: The study is aimed at highlighting the pattern of congenital defect in a tertiary care hospital. Congenital anomalies are recognized as a growing cause of neonatal morbidity and mortality in developing countries and a major cause of distress to parents. Methods: This was a prospective descriptive study conducted between September 2019 and August 2020 with the objective to determine the types of congenital anomalies among live born neonates at Manipal Teaching Hospital (MTH), Pokhara and to determine their immediate outcome. Neonatal and maternal characteristics were noted. Results: Twenty four out of 2515 live births had congenital anomalies during the study period, giving an incidence rate of 9.42 congenital anomalies per 1000 live birth per year. Single system involvement was seen in 79.2 % cases, remaining 5 (20.8%) neonates had involvement of more than one system; 54.2% of these newborns were discharged, 33.3% expired, 8.3% left against medical advice and 4.2% were referred out. Conclusions: This study highlights the importance of clinical examination of neonates to detect anomalies in our setting. Keywords: Congenital anomalies; incidence; newborn